STRATEGI PR PEMERINTAH KABUPATEN BADUNG DALAM KOMUNIKASI PENGELOLAAN SAMPAH MELALUI MEDIA SOSIAL - Ni Kadek Elvina Aprelia Damayanti; Kadek Devi Kalfika Anggria Wardani; I Nyoman Subanda; I Gusti Agung Ananda Putra (Bajang Institute, 2026)
The increasing complexity of waste management problems in Badung Regency, Bali, highlights the urgency of effective government communication strategies to foster public awareness and participation. This study aims to analyze the public relations (PR) strategies employed by the Government of Badung Regency in communicating waste management issues through Instagram. Using a qualitative descriptive approach, data were collected through social media observation, in-depth interviews, and document analysis. The study adopts the Four-Step Public Relations Process and the Two-Way Symmetrical communication model as its analytical framework, supported by Uses and Gratifications Theory, Social Media Engagement, and the Theory of Planned Behavior. The findings indicate that the government’s PR strategy primarily focuses on informative content and activity reporting, while two-way interaction and public participation remain limited. Public responses to waste management messages are categorized into positive, negative, and neutral responses, influenced by factors such as message relevance, content attractiveness, credibility of information sources, and perceived ease of participation. Although Instagram has been utilized as a communication platform, the strategy has not fully succeeded in transforming public awareness into sustained pro-environmental behavior. This study contributes theoretically to the development of government public relations and environmental communication studies, and practically provides recommendations for designing more participatory, interactive, and behavior-oriented communication strategies in local government waste management campaigns